Streptococcus suis-associated neonatal meningitis and sepsis: characterization, antimicrobial resistance, and public health implications - Fusco, Giovanna; Paradiso, Rubina; Cardillo, Lorena; Salvia, Maria Antonia; Dodaro, Saveria; Del Monaco, Veronica; Scarpelli, Gianfranco; Greco, Francesca; Rinaldi, Antonio; Barca, Lorella; Ambrogio, Stefania; Limone, Antonio; et al. (Frontiers in Microbiology, 2025)
Neonatal meningitis and sepsis were diagnosed in a 32-day-old preterm-born infant. Streptococcus (S.) suis was isolated from cerebrospinal fluid and blood. Next-generation sequencing revealed that the strain was serotype 2 sequence type 1, and contained the ermB and tet(W) genes, which are responsible for resistance to macrolides and tetracycline, along with several pilus-associated genes and 20 virulence factors. High homology was observed with previously identified human and swine strains in the same area. S. suis meningitis and sepsis are mainly reported in adults, related to direct contact with pigs or contaminated pork meat consumption, while it is rarely reported in children. Herein, we describe the first case of S. suis in a newborn associated with meningitis and antimicrobial resistance. The rates of resistance to tetracyclines, lincosamides, and macrolides for this bacterium are increasing and are creating concern worldwide. Altogether, our findings highlight the importance of investigating S. suis in cases of neonatal meningitis, as well as the necessity of assessing the antimicrobial profile to obtain useful information for developing targeted therapies.